Portland cement-based multi-component concrete and preparation method thereof

By using modified fiber materials and fly ash in concrete, the multi-component concrete formulation is optimized, and the problem of insufficient fluidity and interface bonding performance of existing composite fiber reinforced concrete is solved, achieving higher mechanical strength and crack resistance.

CN119613059AActive Publication Date: 2025-03-14ZHEJIANG HUAZI BENTENG BUILDING MATERIAL CO LTD

Patent Information

Application Number
CN202510168553.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-03-14
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The existing composite fiber reinforced concrete has shortcomings in fluidity and interface bonding performance, resulting in the concrete structure not being dense enough and unable to effectively improve the mechanical strength and crack resistance.

Method used

Using a multi-component concrete formula based on silicate cement, the formulation is optimized to reduce pore defects in the concrete by physically mixing fly ash and modified fiber materials, and by reasonably controlling the component ratio of each added component.

Benefits of technology

Through the use of modified fiber materials, the connection effect between cement and other components is enhanced, the mechanical strength and crack resistance of concrete are improved, and the proportion of aggregate and aggregate is controlled, which improves the overall strength and rheological properties of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613059A_ABST
    Figure CN119613059A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses portland cement-based multi-component concrete and a preparation method thereof.The portland cement-based multi-component concrete is formed by mixing portland cement serving as a base material and fly ash, fiber materials and the like serving as auxiliary materials, and aluminum silicate fibers are modified by using a polymeric macromolecular modifier, so that the strength of the portland cement-based multi-component concrete is improved; the surface of the aluminum silicate fiber is coated with a large number of polymeric macromolecular modifier molecular chains, the whole prepared fiber material is of a micro-dendritic three-dimensional structure, when the fiber material is mixed with cement and other base materials, the micro-dendritic three-dimensional structure can extend to all areas of a cement matrix to form a mortise and tenon joint type structure, and the strength of the fiber material is improved. Therefore, the self-reinforcing effect is efficiently exerted, and the mechanical strength, the crack resistance and the like of the concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a multi-component concrete based on Portland cement and a preparation method thereof. Background Art

[0002] Concrete, as an indispensable material in modern construction, has gone through a development process from a traditional single component to a modern multi-component. With the advancement of science and technology and the diversification of engineering needs, multi-component concrete has gradually become the preferred material in the construction industry. Generally speaking, the basic composition of concrete includes four basic elements: cement, sand, stone and water. However, in practice, in order to further optimize the specific properties of concrete, such as enhancing its fluidity, increasing its strength or improving its durability, appropriate amounts of admixtures and additives, such as fibers, are often added as needed.

[0003] The invention patent with publication number CN116102319B discloses a composite fiber reinforced concrete and a preparation method thereof, wherein the modified bamboo fiber, carbon fiber and basalt fiber are mixed to form a composite fiber, which is used as an additive to enhance and modify the concrete, thereby improving the mechanical strength of the concrete. However, the fiber has a large specific surface area, which easily leads to poor fluidity of the concrete, and the interface bonding performance between the fiber and the concrete is poor, and a large gap is easily formed between them, resulting in the structure of the concrete after hardening being not dense enough and unable to achieve a good reinforcement effect. Therefore, the fiber needs to be modified to enhance its bonding with other components in the concrete, so that the fiber itself can be effectively enhanced. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a multi-component concrete based on silicate cement and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing multi-component concrete based on silicate cement, the multi-component concrete comprising the following raw materials in parts by weight: 45-50 parts of Portland cement; 5-8 parts of fly ash; 4-10 parts of fiber material; Aggregate 50-60 parts; Aggregate 30-36 parts; 2-4 parts of water reducing agent; 40-60 parts of water; The preparation method comprises the following steps: The first step is to prepare all the raw materials according to the weight proportions; The second step is to place silicate cement, fly ash, fiber material, aggregate and aggregate in a mixer and stir them evenly at a stirring rate of 500-1000r / min, then adjust the stirring rate to 300-500r / min, continue to add water reducer and water and stir for 10-20 minutes.

[0006] As a further solution of the present invention, the silicate cement is 42.5R type ordinary silicate cement or 52.5R type ordinary silicate cement; the fly ash is Class I fly ash or Class II fly ash; the aggregate is fine stone with a particle size of ≤10mm; the aggregate is river sand with a particle size of ≤5mm; and the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.

[0007] As a further embodiment of the present invention, the method for preparing the fiber material specifically comprises the following steps: Step 1: Disperse aluminum silicate fiber in toluene to form a dispersion, then add diisocyanate monomer and tin catalyst to the dispersion, after adding, raise the temperature to 70-80°C, maintain the temperature for 4-6 hours, separate the fiber material, and obtain modified aluminum silicate fiber; Step 2: Add the polymeric macromolecular modifier to N,N-dimethylformamide, stir mechanically to mix, add the modified aluminum silicate fiber, ultrasonically disperse for 20-30 minutes, then increase the temperature to 60-70°C, maintain for 8-12 hours, separate the product, and obtain the fiber material.

[0008] As a further embodiment of the present invention, in step 1, the tin catalyst is any one of dibutyltin diacetate, stannous octoate or dibutyltin dilaurate.

[0009] As a further embodiment of the present invention, in step 1, the diisocyanate monomer is any one of isophorone diisocyanate, toluene diisocyanate or diphenylmethane-4,4'-diisocyanate.

[0010] As a further solution of the present invention, in step 2, the preparation method of the polymeric macromolecular modifier is specifically as follows: Add 4,4'-diaminostilbene-2,2'-disulfonic acid and 2,3-dibromosuccinic acid to 1,4-dioxane, start stirring until a uniform reaction liquid is formed, introduce nitrogen, exhaust the air, then start the heating program, control the heating rate to 3-5°C / min, raise the temperature to 70-80°C, keep stirring for 6-9h, then lower the temperature to 50-60°C, add the acidifying agent to the reaction liquid, continue to keep stirring for 4-8h after the addition, evaporate and remove the solvent, collect the product, and the polymerized macromolecular modifier can be obtained.

[0011] As a further embodiment of the present invention, the molar ratio of the 4,4'-diaminostilbene-2,2'-disulfonic acid to the 2,3-dibromosuccinic acid is 1-1.2:1.

[0012] As a further embodiment of the present invention, the acidifying agent is an alkaline hydroxide aqueous solution with a mass fraction of 20-30%.

[0013] As a further embodiment of the present invention, the alkaline hydroxide is potassium hydroxide or sodium hydroxide.

[0014] A multi-component concrete based on silicate cement is prepared by adopting the preparation method.

[0015] Beneficial effects of the present invention: The present invention adds fly ash and fiber materials and other additives into silicate cement in the form of physical mixing, and at the same time, by reasonably controlling the composition adjustment of each additive component, the formula is further optimized, which can eliminate the defect of a large number of pores that are easily generated during cement coagulation and molding, wherein the addition of fly ash can save costs. The fiber material can utilize the characteristics of its own fibers to enhance the connection effect between silicate cement and other additives, which is conducive to making the internal structure of the concrete more compact, thereby improving the mechanical strength and crack resistance of the concrete. By controlling the ratio of aggregates and aggregates, the rheological properties of concrete are improved, which is conducive to improving the overall strength of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0017] Figure 1 This is the infrared analysis test diagram of the polymer macromolecular modifier. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Preparation Example Preparation of fiber material: Step 1: Disperse 3.5 g of aluminum silicate fiber in toluene to form a dispersion, then add 5 g of diphenylmethane-4,4'-diisocyanate and 0.1 g of stannous octoate to the dispersion, and after the addition, raise the temperature to 75°C, maintain the temperature for 4 hours, separate the fiber material, and obtain modified aluminum silicate fiber; The percentage of isocyanate groups of the modified aluminum silicate fiber was tested according to the titration test method. The specific test method was the hydrochloric acid-di-n-butylamine test method. 0.2g of modified aluminum silicate fiber was used as the titration sample, and 0.1mol / L hydrochloric acid was used as the standard solution. The test results showed that the percentage of isocyanate groups was 6.422%. Step 2: Add 6.5 g of polymeric macromolecular modifier to N,N-dimethylformamide, stir mechanically to mix, then add 3.2 g of modified aluminum silicate fiber, ultrasonically disperse for 30 minutes, then increase the temperature to 65°C, maintain for 9 hours, separate the product, and the fiber material can be obtained.

[0020] The fiber material was again subjected to a hydrochloric acid-di-n-butylamine titration test, and the percentage of isocyanate groups was measured to be 1.184%. It can be inferred that the principle of the above technical scheme is: first, under the action of the tin catalyst stannous octoate, the active isocyanate substituent at one end of the diphenylmethane-4,4'-diisocyanate structure can modify the surface of the aluminum silicate fiber to obtain isocyanate-modified aluminum silicate fiber. Then, under high temperature conditions, the isocyanate group can further react with the blocked primary amine group in the structure of the polymeric macromolecular modifier, thereby modifying the polymeric macromolecular modifier on the surface of the aluminum silicate fiber to obtain the fiber material.

[0021] The preparation method of the polymeric macromolecular modifier is specifically as follows: 1.2 g of 4,4'-diaminostilbene-2,2'-disulfonic acid and 0.8 g of 2,3-dibromosuccinic acid were added to 1,4-dioxane, and stirring was started until a uniform reaction liquid was formed. Nitrogen was introduced and the air was exhausted. Then, the heating program was started and the heating rate was controlled to be 3°C / min. The temperature was raised to 75°C. After stirring for 8 hours, the temperature was lowered to 55°C. 5 mL of a 25% sodium hydroxide aqueous solution was added to the reaction liquid. After the addition was completed, stirring was continued for 6 hours. The solvent was evaporated and removed. The product was collected to obtain a polymeric macromolecular modifier.

[0022] The infrared analysis test of the polymer macromolecular modifier is as follows Figure 1 As shown, 3308cm -1 and 3364cm -1 The absorption peak at 3000 cm is the characteristic absorption peak of NH in primary and secondary amine groups. -1 ~3100cm -1The absorption peak at 1716 cm is the characteristic absorption peak of carbon and hydrogen on the benzene ring skeleton. -1 The absorption peak at 1389 cm is the characteristic absorption peak of C=O of carboxyl group. -1 The absorption peak at 500 cm is the characteristic absorption peak of S=O of sulfonic acid group. -1 ~600cm -1 No C-Br characteristic absorption peak appears at , which can be inferred that the principle of the above scheme is that under the action of sodium hydroxide, the active substituted amino group in the 4,4'-diaminostilbene-2,2'-disulfonic acid structure and the halogen substituent in the 2,3-dibromosuccinic acid structure undergo continuous substitution reactions to form a polymeric macromolecular substance, namely, a polymeric macromolecular modifier. Since an excess of 4,4'-diaminostilbene-2,2'-disulfonic acid is used, the polymeric macromolecular modifier exhibits amino-terminated properties. Example 1

[0023] A multi-component concrete based on silicate cement, comprising the following raw materials in parts by weight: 45 parts of Portland cement; 5 parts of fly ash; 4 parts of fiber material; Aggregate 50 parts; Aggregate 30 parts; 2 parts of water reducing agent; 40 parts water; The method for preparing the multi-component concrete comprises the following steps: The first step is to prepare all the raw materials according to the weight proportions; The second step is to place silicate cement, fly ash, fiber material, aggregate and aggregate in a mixer and stir them evenly at a stirring rate of 500r / min, then adjust the stirring rate to 300r / min, continue to add water reducer and water and stir for 20 minutes.

[0024] Among them, the silicate cement is 42.5R type ordinary silicate cement; the fly ash is Class I fly ash; the fiber material is the fiber material prepared in the preparation example; the aggregate is fine stone with a particle size of 10 mm; the aggregate is river sand with a particle size of 5 mm; the water reducer is SPC-100 polycarboxylic acid water reducer, the same below. Example 2

[0025] A multi-component concrete based on silicate cement, comprising the following raw materials in parts by weight: 46 parts of Portland cement; 6 parts of fly ash; 5 parts of fiber material; Aggregate 55 parts; Aggregate 32 parts; 2.5 parts of water reducing agent; 45 parts water; The method for preparing the multi-component concrete comprises the following steps: The first step is to prepare all the raw materials according to the weight proportions; The second step is to place silicate cement, fly ash, fiber material, aggregate and aggregate in a mixer and stir them evenly at a stirring rate of 600r / min, then adjust the stirring rate to 400r / min, continue to add water reducer and water and stir for 15 minutes. Example 3

[0026] A multi-component concrete based on silicate cement, comprising the following raw materials in parts by weight: 48 parts of Portland cement; 6 parts of fly ash; 8 parts of fiber material; Aggregate 55 parts; Aggregate 35 parts; 3 parts of water reducing agent; 50 parts water; The method for preparing the multi-component concrete comprises the following steps: The first step is to prepare all the raw materials according to the weight proportions; The second step is to place silicate cement, fly ash, fiber material, aggregate and aggregate in a mixer and stir them evenly at a stirring rate of 1000r / min, then adjust the stirring rate to 500r / min, continue to add water reducer and water and stir for 10 minutes. Example 4

[0027] A multi-component concrete based on silicate cement, comprising the following raw materials in parts by weight: 50 parts of Portland cement; 8 parts of fly ash; 10 parts of fiber material; Aggregate 60 parts; Aggregate 36 parts; 4 parts of water reducing agent; 60 parts of water; The method for preparing the multi-component concrete comprises the following steps: The first step is to prepare all the raw materials according to the weight proportions; The second step is to place silicate cement, fly ash, fiber material, aggregate and aggregate in a mixer and stir them evenly at a stirring rate of 1000r / min, then adjust the stirring rate to 500r / min, continue to add water reducer and water and stir for 10 minutes.

[0028] Comparative Example 1 A multi-component concrete based on silicate cement, comprising the following raw materials in parts by weight: 46 parts of Portland cement; 6 parts of fly ash; 5 parts of aluminum silicate fiber; Aggregate 55 parts; Aggregate 32 parts; 2.5 parts of water reducing agent; 45 parts water; The method for preparing the multi-component concrete comprises the following steps: The first step is to prepare all the raw materials according to the weight proportions; The second step is to place silicate cement, fly ash, aluminum silicate fiber, aggregate and aggregate in a mixer and stir them evenly at a stirring rate of 600r / min, then adjust the stirring rate to 400r / min, continue to add water reducer and water and stir for 15 minutes.

[0029] Comparative Example 2 A multi-component concrete based on silicate cement, comprising the following raw materials in parts by weight: 46 parts of Portland cement; 6 parts of fly ash; Aggregate 55 parts; Aggregate 32 parts; 2.5 parts of water reducing agent; 45 parts water; The method for preparing the multi-component concrete comprises the following steps: The first step is to prepare all the raw materials according to the weight proportions; The second step is to place the silicate cement, fly ash, aggregate and aggregate in a mixer and stir them evenly at a stirring rate of 600r / min, then adjust the stirring rate to 400r / min, continue to add water reducer and water and stir for 15 minutes.

[0030] Test Case The concrete in the embodiments and comparative examples was tested for performance, and the results are recorded in Table 1:

[0031] Note: The mechanical strength test refers to the standard GB / T 50081-2019, and the test time is 28 days after the concrete is conventionally cured; the cracking performance test refers to the standard JGJ / T 70-2009; The present invention modifies aluminum silicate fiber by using a polymeric macromolecular modifier so that the surface of the aluminum silicate fiber is coated with a large number of polymeric macromolecular modifier molecular chains, so that the prepared fiber material as a whole presents a micro-branch-like three-dimensional structure. When mixed with base materials such as cement, these branch-like micro-three-dimensional structures will extend to various regions of the cement matrix to form a "mortise and tenon" structure, and then firmly embed into the concrete structure, so that good bonding performance is generated between each other. Since the molecular chain structure of the polymeric macromolecular modifier contains a large number of sulfonic acid and carboxylic acid active substituents, these active substituents can react with calcium hydroxide in the early stage of cement hydration, and greatly improve the hydration rate of tricalcium silicate, thereby inhibiting the phenomenon of forming a loose structure in the early stage of tricalcium silicate hydration, making the connection between cement and aluminum silicate fiber tighter, reducing the porosity of concrete, and thus combining the reinforcement effect of the aluminum silicate fiber itself, so that the prepared concrete exhibits excellent mechanical strength and crack resistance.

[0032] From the analysis of the test results, it can be seen that the use of the fiber material prepared in the preparation example as a concrete additive can make the prepared concrete show excellent mechanical strength and crack resistance. When unmodified aluminum silicate fiber is used instead of fiber material as an additive, the mechanical strength and crack resistance of the concrete are significantly reduced. This is because the gap between the aluminum silicate fiber and the cement and aggregate is large, and the bonding force is not strong, resulting in the aluminum silicate fiber being unable to efficiently play its role. After the aluminum silicate fiber is directly removed, the various properties of the concrete further decline, indicating that the addition of aluminum silicate fiber has a significant positive effect on improving the comprehensive performance of concrete.

[0033] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

[0034] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing multi-component concrete based on Portland cement, characterized in that: The multi-component concrete comprises the following raw materials in parts by weight: 45-50 parts of Portland cement; 5-8 parts of fly ash; 4-10 parts of fiber material; Aggregate 50-60 parts; Aggregate 30-36 parts; 2-4 parts of water reducing agent; 40-60 parts of water; The preparation method comprises the following steps: The first step is to prepare all the raw materials according to the weight proportions; The second step is to place silicate cement, fly ash, fiber material, aggregate and aggregate in a mixer and stir them evenly at a stirring rate of 500-1000r / min, then adjust the stirring rate to 300-500r / min, continue to add water reducer and water and stir for 10-20 minutes.

2. The method for preparing a multi-component concrete based on Portland cement according to claim 1, characterized in that: The silicate cement is 42.5R type ordinary silicate cement or 52.5R type ordinary silicate cement; the fly ash is Class I fly ash or Class II fly ash; the aggregate is fine stone with a particle size of ≤10mm; the aggregate is river sand with a particle size of ≤5mm; the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.

3. The method for preparing a multi-component concrete based on Portland cement according to claim 1, characterized in that: The preparation method of the fiber material specifically comprises the following steps: Step 1: Under the action of a tin catalyst, the aluminum silicate fiber is surface-modified using a diisocyanate monomer to obtain a modified aluminum silicate fiber; Step 2: Using N,N-dimethylformamide as a medium, further modifying the modified aluminum silicate fiber with a polymeric macromolecular modifier can produce a fiber material.

4. The method for preparing a multi-component concrete based on Portland cement according to claim 3, characterized in that: In step 1, the tin catalyst is any one of dibutyltin diacetate, stannous octoate or dibutyltin dilaurate.

5. The method for preparing a multi-component concrete based on Portland cement according to claim 3, characterized in that: In step 1, the diisocyanate monomer is any one of isophorone diisocyanate, toluene diisocyanate or diphenylmethane-4,4'-diisocyanate.

6. The method for preparing a multi-component concrete based on Portland cement according to claim 3, characterized in that: In step 2, the preparation method of the polymeric macromolecular modifier is specifically as follows: Add 4,4'-diaminostilbene-2,2'-disulfonic acid and 2,3-dibromosuccinic acid to 1,4-dioxane, start stirring until a uniform reaction liquid is formed, introduce nitrogen, exhaust the air, then start the heating program, control the heating rate to 3-5°C / min, raise the temperature to 70-80°C, keep stirring for 6-9h, then lower the temperature to 50-60°C, add the acidifying agent to the reaction liquid, continue to keep stirring for 4-8h after the addition, evaporate and remove the solvent, collect the product, and the polymerized macromolecular modifier can be obtained.

7. The method for preparing a multi-component concrete based on Portland cement according to claim 6, characterized in that: The molar ratio of the 4,4'-diaminostilbene-2,2'-disulfonic acid to 2,3-dibromosuccinic acid is 1-1.2:

1.

8. The method for preparing a multi-component concrete based on Portland cement according to claim 6, characterized in that: The acidifying agent is an alkaline hydroxide aqueous solution with a mass fraction of 20-30%.

9. The method for preparing a multi-component concrete based on Portland cement according to claim 8, characterized in that: The alkaline hydroxide is potassium hydroxide or sodium hydroxide.

10. A multi-component concrete based on Portland cement, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite fiber reinforced concrete and preparation method thereof

    CN116102319B

  • Polymer-tempered dry construction material mixtures

    CN101679118A

  • High-strength concrete and preparation process thereof

    CN110590288A

  • Phosphorus-free fluorescent scale and corrosion inhibitor and preparation method thereof

    CN113860522A

  • Impermeable recycled concrete and preparation method thereof

    CN114477919A

Cited By

  • Preparation method and application of cement-based composite phase change grouting material

    CN120136503A

  • Preparation method and application of cement-based composite phase change grouting material

    CN120136503B

  • Ultra-high performance concrete based on replacement of mineral admixture by dry-wet process and multi-scale ground graphite tailings and preparation method of ultra-high performance concrete

    CN122403895A